RECORDING OF THE CHANGES OF THE NATURAL GEOMORPHOLOGICAL ENVIRONMENT USING MAPS OF DIFFERENT ISSUE DATE. AN EXAMPLE FROM THE COASTAL ZONE OF THE SOUTH-WESTERN ATTICA - Βερυκίου-Παπασπυριδάκου, Ε.; Σκυλοδήμου, Χ.; Μπαθρέλλος, Γ. (Bulletin of the Geological Society of Greece, 2018)
This paper deals with the recording of the changes of the natural géomorphologie environment of the southwestern coastal zone of Attica through the comparison of two different series of maps. The first series is dated from 1882 until 1887 and the second is a recent one by the Geographic Military Service (GMS). Thirteen different regions were studied in total. When studying and comparing the regions on the maps along with the on site research, we observed that the natural geographical features of the coastal zone have been altered via the human interference. To be more specific, the coastal dunes have almost vanished and the old lagoons have been dried or banked up. Finally, the surface covered by the coastal dunes and the lagoons was also measured. It is remarkable to add that the whole region is characterized by intense filling up, artificial expansion of the land against the sea, dense construction of buildings, important tourist development, changes of the land use, public works, riverbed management and disappearance of the past flora and the forestry areas.